2021
DOI: 10.1053/j.gastro.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopist Performance and Colorectal Cancer Risk After Adenoma Removal to Stratify Surveillance: Two Nationwide Observational Studies

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e19. Learning Objective: Upon completion of this CME activity successful learners will be able to identify limitations of the metrics used to evaluate colonoscopy performance and describe how current metrics relate to interval colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…However, we suspect that the number of symptomatic interval cancers was quite small for both groups given the relatively high ADR of the participating endoscopists. 27 Seventh, the retrospective design also precludes a detailed analysis of the extent to which differential exposure to risk factors for polyp recurrence other than age, sex, and socioeconomic status may have influenced our results. 28,29 Lastly, we relied on the subjective judgment of multiple endoscopists to provide data about polyp size, thereby raising the possibility of misclassification for ACN defined by size alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, we suspect that the number of symptomatic interval cancers was quite small for both groups given the relatively high ADR of the participating endoscopists. 27 Seventh, the retrospective design also precludes a detailed analysis of the extent to which differential exposure to risk factors for polyp recurrence other than age, sex, and socioeconomic status may have influenced our results. 28,29 Lastly, we relied on the subjective judgment of multiple endoscopists to provide data about polyp size, thereby raising the possibility of misclassification for ACN defined by size alone.…”
Section: Discussionmentioning
confidence: 99%
“…CRC detection during surveillance depends not only on the characteristics of the polyps but also on the endoscopist’s technical ability. A recently published Polish study reveals that long-term risk of CRC is increased (HR 2.69, 95% CI: 1.62–4.47) if baseline colonoscopy is performed by low-performing endoscopists (adenoma detection rate <20%) [ 25 ]. In this sense, Spanish CRC screening programs initiate surveillance after a complete evaluation of colonic mucosa and resection of colonic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CRC detection during surveillance depends not only on the characteristics of the polyps but also on the endoscopist’s technical ability. A recently published Polish study revealed that long-term risk of CRC is increased (HR 2.69, 95%CI: 1.62-4.47) if baseline colonoscopy is performed by low-performing endoscopists (adenoma detection rate < 20%)[ 64 ].…”
Section: Fit In Surveillance After Adenoma Resectionmentioning
confidence: 99%